Constipation - a patient's discomfort or a disturbing symptom - an overview of current knowledge - Kuziemkowska, Daria; Ben Rhaiem, Rami; Kępka, Przemysław; Kuźma, Jan; Łącka-Majcher, Anna; Łokczewska-Bojar, Aleksandra; Tarsa, Grzegorz; Skotalczyk, Magdalena; Sawińska, Zuzanna; Sudelska, Katarzyna (Journal of Education, Health and Sport, 2023)
Introduction: Constipation is identified as too few bowel movements (≤2/week; severe constipation is ≤2 bowel movements per month) or hard stools (Bristol Formation Scale 1 and 2) that are passed with effort, often with a sensation of incomplete defecation . Purpose of study: The aim of this review is to present key aspects of constipation, including epidemiology, diagnosis, management and clinical treatment directed to the individual patient and individual therapy. Materials and methods: The review was based on the available literature in the PubMed database and the Google Scholar search engine using the key words: "constipation"; “constipation diagnosis”; “constipation treatment”. Conclusions: Constipation is a common health problem that affects people of all ages. It is the most frequently reported ailment in gastroenterological practice. Not only are they a cause of patient discomfort, but they are often an alarming symptom of a larger pathology in the human body. Correct diagnosis often includes multi-aspect diagnostics, in which doctors of various specialties are involved, and correct treatment significantly improves the quality of life of patients.